Long Non-coding RNA SNHG17 Upregulates RFX1 by Sponging miR-3180-3p and Promotes Cellular Function in Hepatocellular Carcinoma - Ma, Tao; Zhou, Xujun; Wei, Hailiang; Yan, Shuguang; Hui, Yi; Liu, Yonggang; Guo, Hui; Li, Qian; Li, Jingtao; Chang, Zhanjie; Mu, Xiao-Xin (Frontiers in Genetics, 2021)
Background: Hepatocellular carcinoma (HCC) is one of the most common types of cancer that is associated with poor quality of life in patients and a global health burden. The mechanisms involved in the development and progression of HCC remain poorly understood. Methods: Hepatocellular carcinoma human samples and cell lines were subjected to qRT-PCR for expression assessment. CCK-8 assay, Transwell migration and invasion assay, were applied for cell function detection. Animal experiment was used to measure the function of SNHG17 on cell growth in vivo. Western blot was conducted to evaluate the level of EMT in cells. RIP, RNA pull-down and luciferase reporter assays were performed to assess the correlation between SNHG17, miR-3180-3p and RFX1. Results: Our study demonstrated that SNHG17 was upregulated in HCC human samples and involved cell proliferation, migration, invasion progress. SNHG17 promoted HCC cell growth and metastasis in vivo. Furthermore, we investigated the downstream factor of SNHG17, SNHG17 acted as a molecular sponge for miR-3180-3p, and SNHG17 regulated RFX1 expression via miR-3180-3p. SNHG17 promotes tumor-like behavior in HCC cells via miR-3180-3p/RFX1 Conclusion: We determined RFX1 as the target of miR-3810-3p; SNHG17 enhanced the progression of HCC via the miR-3180-3p/RFX1 axis. Taken together, our findings may provide insight into the molecular mechanism involved in the progression of HCC and develop SNHG17 as a novel therapeutic target against HCC.